Standarization of Simplicia and Extracts from Guava leaf (Psidium guajava) - Suswidiantoro, Vicko (Universitas Aisyah Pringsewu, 2025)
The guava leaf (Psidium guajava) is a plant with promise for development as a natural remedy. This work seeks to develop standardization encompassing both specific and non-specific properties of simplicia and extracts. The procedure for establishing standardization parameters pertains to the Indonesian Herbal Pharmacopoeia and General Standard Extracts Parameters. The organoleptic standardization of simplicia is characterized by a brownish-green hue, a unique aroma, and a bitter taste. The water content test revealed a result of 50.4%; the free ethanol content; and a total ash content of 4.06%; the extract standardization indicates a viscous green-black extract with a strong odor and a bitter flavor. The leaves of Psidium guajava include tannins, flavonoids, saponins, and terpenoids. Additional statistics include an extract yield of 20.96%, a moisture content of 40.93%, and a total ash content of 41.18%. The standardization specifications for total ash content and moisture content are not mandated by Media Materia Indonesia or the Republic of Indonesia Drug and Food Control Center)